Destination Marketing : Promoting Cappadocia in terms of heritage and culture - Çizmeci, Zeynep (2019)
Marketing is the whole of actions to promote or increase sales a product or service. Destination marketing is the whole of marketing methods used to increase the visibility of a particular destination, to accelerate its development and to increase the number of visitors. In this context, development of heritage and culture tourism in Turkey will contribute to popularity of Turkey’s tourism. At this point, Cappadocia is one of the most important destination in Turkey in terms of heritage and culture tourism which has significant potential to receive more visitors. The historical background of Cappadocia, the multicultural structure, the fairy chimneys, the subterranean cities with a unique texture, offers a unique experience to its visitors in terms of heritage and culture tourism. At this point, Cappadocia should be promoted in the international and local tourism in order to increase its recognition in competitive tourism industry by applying accurate destination marketing methods. Towards the marketing methods using the Cappadocia's contribution to development, will help Turkey's heritage and culture tourism to play a more active role in this field.